Utilization of Artificial Intelligence-Based Canva as an Adaptive Learning Media for Students with Intellectual Disabilities - Fauzi, Ali; Eriyanti, Ribut Wahyu; Sunaryo, Hari (Universitas Islam Negeri Raden Intan Lampung, 2026)
Students with intellectual disabilities frequently encounter cognitive and adaptive learning barriers that require structured, visual, and personalized instructional support within inclusive education environments. Despite the rapid advancement of artificial intelligence (AI) technologies in education, limited studies have examined the pedagogical potential of AI-supported design platforms such as Canva for adaptive learning in this population. This study aims to analyze the role of AI-based Canva as an adaptive learning medium for students with intellectual disabilities through a systematic literature review combined with thematic analysis of recent research on AI integration, visual learning media, and inclusive instructional practices. The findings indicate that AI-supported Canva facilitates material simplification, multimodal visualization, and flexible content personalization that enhance student engagement, conceptual understanding, and accessibility of learning materials while supporting teachers in implementing differentiated instruction. In addition, the platform contributes to improving instructional efficiency and promoting inclusive learning environments when supported by adequate pedagogical planning and digital literacy competencies. This study contributes to the literature by proposing a conceptual framework for integrating AI-based Canva as an adaptive visual learning medium in inclusive education contexts and provides practical guidance for educators and policymakers in designing accessible technology-enhanced instruction for students with intellectual disabilities.